IMPROVING MECHANICAL AND THERMAL PROPERTIES FOR UNSATURATED POLYESTER RESIN BY ADDING GYPSUM - Angham Elias Abdul Muhsen, Prof. Dr. Ebtahag Z. Sulyman, (Chelonian Research Foundation, 2024)
This research aims to prepare polymeric composites of unsaturated polyester as a base material for gypsum. Then, their mechanical properties were studied by measuring (hardness, compressive strength, impact resistance, modulus of elasticity). To achieve this goal, samples with different weight percentages of gypsum were prepared, and the addition percentage was from (5%-50%). The study showed an increase in the properties. Mechanical increase in the percentage of reinforcement, and the best percentage was at 30%, and the addition was done at different temperatures (8, 25, 50)°C. After comparing unsaturated polyester before and after reinforcement of the prepared compounds, it was found that there was an increase in all mechanical properties after reinforcement with gypsum at (8,25,50)°C, except for the modulus of elasticity, which decreased at all temperatures. It was also found that the thermal conductivity decreased at temperatures (8, 25, and 50)°C, which indicates that polymeric compounds consisting of unsaturated polyester resins reinforced with gypsum are good thermal insulators.